2018
DOI: 10.3389/fpsyg.2018.01803
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blurred Perceptual Training on the Decision Making of Skilled Football Referees

Abstract: When judging ambiguous foul situations in football (soccer), referees must attune to the kinematic characteristics inherent in genuine fouls to ensure that they can (i) recognize when a foul has taken place, and (ii) discriminate the presence of deceptive intent on the part of the tackled player. The aim of this study was to determine whether perceptual training that removes superficial visual information would improve the decision-making performance of football referees. Two groups of skilled referees judged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…Skilled observers would be expected to already be more proficient in their ability to anticipate deceptive actions ( Jackson et al, 2006 ), and so it is often considered to be more challenging to improve the already high anticipatory skill of better performers. Nonetheless, a concurrent study by van Biemen et al (in review) has provided some suggestion that blurred perceptual training might also improve the decision making performance of skilled observers. In that study, evidence was found to suggest that the ability of skilled football referees to discriminate deceptive from non-deceptive actions (fouls vs. ‘dives’ in football) improved as a result of training when viewing blurred actions.…”
Section: Discussionmentioning
confidence: 99%
“…Skilled observers would be expected to already be more proficient in their ability to anticipate deceptive actions ( Jackson et al, 2006 ), and so it is often considered to be more challenging to improve the already high anticipatory skill of better performers. Nonetheless, a concurrent study by van Biemen et al (in review) has provided some suggestion that blurred perceptual training might also improve the decision making performance of skilled observers. In that study, evidence was found to suggest that the ability of skilled football referees to discriminate deceptive from non-deceptive actions (fouls vs. ‘dives’ in football) improved as a result of training when viewing blurred actions.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies assessed decision accuracy changes in central officials' subjective judgements of one‐on‐one player contact decisions (football, n = 3; Australian rules football, n = 2; rugby union, n = 1) and of novice students' subjective decisions regarding player contact situations (“Swirl ball,” n = 1). Of the six central official training studies, four studies yielded an average percentage accuracy improvement of 5.9% (min = 4%, 56 max = 8.4% 37 using video‐based methods). One study showed an 8.1% improvement in decision accuracy in context‐specific decisions compared to not, 5 while two other studies found significant differences in decision accuracy improvement between skill groups (17.4%, low‐ranked developing and 3.6%, high‐ranked expert officials 37 ; 8%, less‐experienced, and 2%, more experienced sport officials 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies primarily used isolated video decision situations (from a 3 rd person perspective) as the mode to train perceptual‐cognitive skills. Some training studies manipulated perceptual information presented in such videos through blurring perceptual information 56 , adjusting the temporal ordering of decision situations (i.e., mixed vs. in context) 5 , and altering video speed 60 . Recommedations for future video‐based approaches include manipulating the difficulty of decision situations presented 34 and training visual search strategies 74 …”
Section: Discussionmentioning
confidence: 99%
“…However, video analysis has also been introduced into various sport settings for other beneficial purposes, such as into stadia to help officials make on-field decisions regarding the scoring of goals, tries or points. They also help them to review and adjudicate potential illegal actions by athletes during competitive events and then whether or not to issue various penalties, such as red, yellow or black cards in sports such as soccer, rugby, tennis, basketball and Gaelic football for example ( van Biemen et al, 2018 ; Sors et al, 2019 ). Video play back has also become part of the normal spectator and fan-experience when watching sport, either from their homes or in person in stadia during breaks in competition or play ( Arkenberg et al, 2019 ).…”
Section: Video Analysis Technology Usementioning
confidence: 99%